The Effectiveness of the Gidden’s Structural Theory in Creating the Eco-Friendly, Sustainable and Green Economy Through Energy Flow for Maize Production Management - Latifah Abdul Ghani, Noor Zalina Mahmood, Jumadil Saputra, Syaiful Bahri, Zikri Muhammad (International Journal of Advanced Science and Technology, 2020)
The primary purpose of this current study is to investigate the extent to which the effectiveness of the Gidden’s Structural Theory based Material Flow Analysis approach in creating an eco-friendly, sustainable and green economy through energy flow for Maize production management. A total of 10 farms exceeding the 50-hectares of land were involved as study samples and the biomass energy from maize production waste was selected as a parameter of the study. The data was analysed using the software SubTANce Analysis (STAN) 2.5, ArcGIS and Microsoft Excel. The results of the study show that there is a continuous and significant relationship in the acquisition of biomass energy flow data in the proposed integrated framework model. These results in this manner support the fact that biomass energy balance data in the production of maize residue can be evaluated through a computational and correlative calculation method. The study also identified the change agents involved concretely in developing a more efficient and effective governance system for the management of maize productivity and its residual waste.